Таргетування інфляції в країнах з середніми та низькими доходами: традиційні дилеми та посткризові виклики - Козюк, Віктор; Koziuk, Viktor (ТНЕУ, 2019)
Вступ. Досліджено питання імплементації режиму інфляційного таргетування в країнах з ринками, що формуються. Подальші дослідження в цьому напрямку актуалізовані викликами реалізації таргетування інфляції в складному макроекономічному й інституціональному середовищі. Спираючись на огляд робіт з питань теорії і практики реалізації монетарного режиму, виокремлено низку ключових узагальнень. Мета – показати зміни в поглядах на інфляційне таргетування в країнах з ринками, що формуються, а також виокремити ключові виклики цьому режиму в світлі їх економічного та фінансового розвитку, а також в контексті глобальної інтеграції. Результати. Проведено узагальнення основних сучасних тенденцій довкола реалізації політики інфляційного таргетування в країнах з ринками, що формуються. Виокремлено кілька принципових царин, довкола яких точаться найбільші дискусії і де має місце істотний прогрес в ефективності монетарної політики: зв’язок цінової та курсової стабільності; проблема реакції на шоки пропозиції; інституціональні драйвери відхилення від цілей; поєднання інфляційного таргетування з макропруденційною політикою. Стверджується, що чим швидше країна просувається на шляху реформ, тим більше послаблюється зв’язок між ціновою та курсовою стабільністю, а шоки умов торгівлі більше нагадують шоки на боці пропозиції. Водночас констатується, що центробанки країн з ринками, що формуються, не можуть оптимально ігнорувати такі шоки через характер інфляційних очікувань. Реакція на шоки пропозиції буде тим менш про-циклічною, чим більшою мірою центробанки користуються довірою, а фінансова система є більш глибокою. Висновки. Поєднання інфляційного таргетування та проактивної макропруденційної політики дасть змогу покращити макроекономічну картину в країнах з ринками, що формуються. Introduction. It is focused on the problem inflation targeting regime evolvement in emerging market countries. The generalization of key problems is done relying on literature review and overview of empirical works. Purpose of the paper is to show how the way of thinking about inflation targeting in emerging market countries is changed according to they economic and financial development as well as they connections with global economy. It is distinct some the most disputable and progress-made arrears of inflation targeting in less developed countries: connections between price and exchange rate stability; reactions on the supply-side shocks; institutional drivers of deviations from the targets; co-integration between inflation targeting and macroprudential policy. It is fount the more country advanced in the structural reforms the less sensitive price stability to exchange rates movements is and term-of-trade shocks more resemble supply-side shocks. But central banks from emerging market countries couldn’t stay neglect of supply-side shocks because of more sensitive inflation expectations to core-inflation reaction on non-core inflation behavior. While commodity shocks may easily deteriorate movements of the most volatile components of price index supply-side shocks are more like persistent in nature. Not to react on them according to orthodox New-Keynesian theory is very risky especially then inflation expectations are not strongly anchored. Results. Deviations from inflation targets are viewed from institutional position meaning that political environment as well as factual central bank’s independence is important and markets flexibility, that minimizes costs of stronger reaction on price shocks, is a consequence of structural reforms. Financial stability in emerging markets is viewed from capital flows and exchange rates volatility perspective that may bring additional conflicts with inflation targets. Conclusions. It is stressed that monetary policy in emerging markets will benefited from more active approach on financial imbalances. That is why inflation targeting with pro-аctive macroprudential policy is shown as example of relevant policy-mix for better macroeconomic performance.
Inflation targeting in the countries with middle and low income: traditional dilemes and post-crisis challenges
Keywords: інфляційне таргетування; центральні банки; монетарна політика; цінова стабільність; шоки пропозиції; країни з ринками, що формуються.; inflation targeting; central banks; monetary policy; price stability; supply-side shocks; emerging market countries